Promoting anti-racism in the legal system: an application of the STYLE framework - Fix, Rebecca L.; Thurston, Idia B.; Johnson, Renee M.; Andrisse, Stanley (Frontiers in Psychology, 2023)
Racism is a critical social problem, and we present a framework to guide professionals in engaging in anti-racist practices. Professionals on the frontlines in psychology and related fields such as social work and public health have a responsibility to engage in anti-racist practices. Part of the professional role must be to advocate for justice through increased proximity to the issues and engagement in anti-oppressive practices. The current discourse introduces a framework through which psychology and other related professions can promote anti-racism work, highlighting the legal system for illustrative purposes. While some professionals in psychology may not have direct experience with the legal system, many of the individuals served by psychologists do (e.g., clients/patients, students, community members). Our framework is represented by the acronym STYLE (Self-examination, Talk about racism, Yield time to antiracism work, Learn about structural racism, Evaluate policies and practices). The goal of STYLE is to expand anti-racism science and practice within psychology and related fields. We describe new roles for professionals in dismantling health inequities and offer specific pathways to develop critical partnerships toward this aim. STYLE explicitly encourages active, intentional involvement of affected community members in the development and evaluation of approaches to health services. To achieve equity and to promote individual and organizational growth in anti-racism and ultimately anti-oppression work, professionals must focus on changing their STYLE.